Experimental Evaluation of Strength Degradation of Orthodontic Chain Elastics Immersed in Hot Beverages. Issue 4 (October 2019) - Braga, Emanuel; Souza, Gabriella; Barretto, Paula; Ferraz, Caio; Pithon, Matheus
Abstract: Introduction: Elastomeric chains are relevant in orthodontic mechanics due to the form memory property; however, elastomers present high force reduction in some circumstances. The objective was to evaluate the effect of hot beverages on tensile strength degradation of orthodontic elastomeric chains. Material and Methods: Four groups were tested according to different immersion liquids: artificial saliva (group 1), hot water (group 2), green tea (group 3), and coffee (group 4). The elastomeric chains of groups 2, 3, and 4 were immersed in the respective liquids, with temperature of 70 ± 1°C twice daily for 30 seconds for a period of 7, 14, or 21 days. All samples were kept in artificial saliva and stored in an incubator at controlled temperature of 37 ± 1°C. The elastomeric chains were then examined in the testing machine (AME-2kN; Filizola, São Paulo, Brazil) to measure the tensile strength degradation. Results: It was observed through intragroup comparisons that the control showed a progressive reduction of tensile strength in a statistically significant manner throughout the study period. In turn, the hot water, green tea, and coffee samples showed a statistically significant reduction from 7 to 14 days. From 14 to 21 days, the tension remained stable. When the test groups were compared with the control, it was observed that all groups presented tension reduction in a statistically significant manner at all periods, except for the coffee group at 21 days ( P < .001). Conclusions: Experimental immersion in hot water, green tea, and coffee at 70 ± 1°C contributed in a statistically significant manner to the strength degradation of orthodontic elastomeric chains in the period of 7 and 14 days.